Resonance and generation of random states in a quenched Ising model - Mishra S.K.; Lakshminarayan A. (My University, 2025)
The Ising model with a pulsed transverse and a continuous longitudinal field is studied. Starting from a large transverse field and a state that is nearly an eigenstate, the pulsed transverse field is quenched with a simultaneous enhancement of the longitudinal field. The generation of multipartite entanglement is observed along with a phenomenon akin to quantum resonance when the entanglement does not evolve for certain values of the pulse period. Away from the resonance, the longitudinal field can drive the entanglement to near maximum values that is shown to agree well with those of random states. Further evidence is presented that the time-evolved states obtained do have some statistical properties of such random states. For contrast the case when the fields have a steady value is also discussed. © Copyright EPLA, 2013.